Influence of Fe2+ and Fe3+ on the growth of Leptospirillum ferriphilum CC and oxidation of Fe2+ - Khachatryan, A. C. (ՀՀ ԳԱԱ հրատ.)
In the paper kinetics of ferrous iron oxidation by isolated Leptospirillum ferriphilum CC was studied in conical flasks on rotary shaker. The effect of initial ferrous iron concentration on bacterial growth and substrate oxidation was studied in the concentration range of 50-400 mM FeSO4 x7H2O. The highest specific growth (0.41- 0.48 h1) and Fe2+ oxidation rates (6.0-6.2 mM/l h) were detected at ferrous ion concentrations of 100-200 mM. At higher concentrations, the growth of bacteria and Fe2+ oxidation suppression was observed, reaching maximum values at 400 mM Fe2+. The maximum specific growth rate (µmax) of bacteria and half saturation constant (Ks) determined using Monod equation were 6.2mM /h, and 0.83h-1, respectively. It was shown that Fe2+ oxidation competitively inhibited by Fe3+ and the inhibition constant (Ki) was 61.95 mM. The comparison of kinetic parameters obtained for L. ferriphilum with other bacteria indicates the high potential of L.ferriphilum CC in leaching processes of ores and concentrates for biogenic regeneration of concentrated ferric iron. Հոդվածում ուսումնասիրվել է երկարժեք երկաթի օքսիդացման կինետիկան մեկուսացված Leptospirillum ferriphilum CC-ի մոտ 250 մլ Էրլենմեյերի կոլբաներում թափահարման պայմաններում: Երկարժեք երկաթի սկզբնական կոնցենտրացիաների ազդեցությունը բակտերիայի աճի և սուբստրատի օքսիդացման վրա ուսումնասիրվել է FeSO4x7H2O 50-400 մՄ կոնցենտրացիաների միջակայքում: Բակտերիայի աճի առավելագույն տեսակարար արագությունը (0.41-0.48 ժ -1 ) և սուբստրատի օքսիդացման առավելագույն արագությունը (6.0-6.2 մՄ/լ ժամ) դիտվել է FeSO4 x7H2O-ի 100-200 մՄ կոնցենտրացիայի պայմաններում: Ավելի բարձր կոնցենտրացիաների դեպքում դիտվել է բակտերիայի աճի և երկաթի օքսիդացման ճնշում, որն առավելագույն մեծության է հասել 400 մՄ-ի դեպքում: Մոնոյի հավասարման կիրառմամբ որոշված բակտերիայի աճի առավելագույն տեսակարար արագության (µmax) և հագեցման հաստատունի (µmax) արժեքները կազմել են 6.2 մՄ/ժ, և 0.83 ժ -1 համապատասխանաբար: Ցույց է տրվել, որ եռարժեք երկաթի իոնները մրցակցորեն ճնշում են երկաթի օքսիդացումը, ճնշման հաստատունը (Ki) կազմել է 61.95 մՄ: L. ferriphilum-ի և այլ բակտերիաների կինետիկական պարամետրերի համեմատությունը վկայում է առաջինի մեծ ներուժի մասին հանքաքարերի և խտանյութերի տարրալուծման գործընթացում՝ եռարժեք երկաթի կենսածին վերականգնման համար:
Keywords: Biology; Biochemistry